1999
DOI: 10.1006/dbio.1999.9415
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Release at Fertilization of Xenopus Eggs Requires Type I IP3 Receptors, but Not SH2 Domain-Mediated Activation of PLCγ or Gq-Mediated Activation of PLCβ

Abstract: Elevation of intracellular Ca2+ at fertilization is essential for the initiation of development in the Xenopus egg, but the pathway between sperm-egg interaction and Ca2+ release from the egg's endoplasmic reticulum is not well understood. Here we show that injection of an inhibitory antibody against the type I IP(3) receptor reduces Ca2+ release at fertilization, indicating that the Ca2+ release requires IP(3). We then examine how IP(3) production is initiated. Xenopus eggs were injected with specific inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
108
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(112 citation statements)
references
References 84 publications
4
108
0
Order By: Relevance
“…Phenotypic analysis of such a mutant is needed to definitively conclude whether or not PLC serves as the trigger for Ca 2ϩ release in mouse. The specific PLC isoform used in Xenopus has not been resolved; PLC␥ is present and active (phosphorylated) in fertilized eggs, but its activation does not appear to occur through an egg SFK (Runft et al, 1999;Sato et al, 2000). There is some evidence for a sperm-derived PLC in Xenopus because sperm extracts from Xenopus can induce an increase in Ca 2ϩ upon injection into mouse eggs (Dong et al, 2000).…”
Section: Triggers Of Egg Activation Spermmentioning
confidence: 99%
“…Phenotypic analysis of such a mutant is needed to definitively conclude whether or not PLC serves as the trigger for Ca 2ϩ release in mouse. The specific PLC isoform used in Xenopus has not been resolved; PLC␥ is present and active (phosphorylated) in fertilized eggs, but its activation does not appear to occur through an egg SFK (Runft et al, 1999;Sato et al, 2000). There is some evidence for a sperm-derived PLC in Xenopus because sperm extracts from Xenopus can induce an increase in Ca 2ϩ upon injection into mouse eggs (Dong et al, 2000).…”
Section: Triggers Of Egg Activation Spermmentioning
confidence: 99%
“…The Ca 2þ wave is followed by a sustained Ca 2þ plateau that lasts for several minutes (Busa and Nuccitelli, 1985;El Jouni et al, 2005). The Ca 2þ wave is due to Ca 2þ release from intracellular stores through the IP 3 receptor (IP 3 R), since it is inhibited by blocking IP 3 -dependent Ca 2þ release or PIP2 hydrolysis (Larabell and Nuccitelli, 1992;Nuccitelli et al, 1993;Runft et al, 1999). Moreover, a wave of IP 3 has been proposed to precede the Ca 2þ release wave in eggs at fertilization (Wagner et al, 2004).…”
Section: Spatial and Temporal Dynamics Of Ca 2r Signals During Maturamentioning
confidence: 99%
“…PLCc isozymes are thought to operate in ascidian and echinoderm fertilization, as it was shown that injection of excess PLCc SH2 domain, acting in a dominant negative manner, prevented sperm-induced [Ca 2+ ] i release in eggs of these species (Carroll et al, 1997Shearer et al, 1999;Runft and Jaffe, 2000). On the contrary, using a similar approach, it was shown that [Ca 2+ ] i release in Xenopus and mouse fertilization occurred unperturbed in the presence of excess SH2 domains, suggesting that PLCc activation is not important in these species, or that it occurs by a different mechanism Runft et al, 1999). Toward this end, it is worth noting that injection of recombinant PLCc1 protein into mouse eggs resulted in the generation of fertilization-like [Ca 2+ ] i oscillations (Mehlmann et al, 2001).…”
Section: Plccmentioning
confidence: 99%